Dampak Kenaikan Harga Gas LPG 3 Kg terhadap Kemampuan Rumah Tangga Miskin Dalam Pemenuhan Kebutuhan Hidup di Kelurahan Alalak Utara Kecamatan Banjarmasin Utara - Yulia Permata Sari; Chairul Sa’roni (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
The purpose of this study is to determine the amount of household expenditure thatmust be spent due to the 3kg LPG price increase, know the efforts of low households whenthere is an increase of 3kg LPG and to see the difference before or after the 3 kg LPG priceincrease in the North Alalak area North Banjarmasin. This research was conducted on lowhouseholds in the northern alalak village, Banjarmasin north. The data used in the study areprimary data and secondary data. This study's population were all low households in thenorthern alalak of Banjarmasin, which amounted to 1112 needy families. Whereas thenumber of samples can be obtained using the Yamane taro formula. Ninety-two respondentswill be selected using simple random sampling techniques or simple random models. Eachsampling unit in the population has the same opportunity to be chosen as a sample member.The study used a paired sample T-test. The t is equal to -9,279, smaller than T's cost, whichis equivalent to 0.67720 with a significance value of 0.000 (p <α). The test results can beconcluded that there are differences between before and after the increase in 3 kg LPG inNorth Alalak Village, North Banjarmasin.